EFEKTIVITAS MODEL PEMBELAJARAN BERORIENTASI KOMPETENSI BERBASIS INTERAKSI AFEKSIONAT (MABKBIA) DALAM MENINGKATKAN MUTU HASIL BELAJAR BAHASA INDONESIA :Sebuah Studi Eksperimental Kuasi dalam Pembelajaran Bahasa Indonesia di SLTP KORPRI Unit Universitas Pendidikan Indonesia - Suherdi, Didi (2004)
This study is concerned with the effectiveness of Competence-oriented, Affectionate-interaction-based Model of Teaching which, in Bahasa Indonesia, may be abbreviated to "MABKBIA" in increasing students' learning achievement, including language mastery, learning participation factors as well as affective factors in learning Bahasa Indonesia. This focus is critical for on the one hand, in Indonesian pedagogic history there is a continuing demand of not-only-effective but also context-sensitive model in the part of our schooling system; on the other hand, combining product-oriented and comfortable process is one is the most promising approach to Indonesian learning society. To guarantee the comprehensiveness of its findings, a quasi experimental design was employed, i.e. that what Grotjahn (1987, as cited by Nunan, 1992) calls experimental-qualitative-statistical design. The qualitative aspect of this design was used to obtain finely-grained details of PBM-MABKBIA implementation. In the meantime, the statistical aspect was to obtain objective quantitative data of its effectiveness in comparison with the conventional PBM. For the purpose of its experimentation, three grade-two classes were selected and randomly assigned to serve the functions of experimental groups and control one. The first class was then decided to be the model class, while each of the other two was assigned to be the experimental and control group in the quantitative quasi randomized pre-test-post-test experimental design. The data obtained were then analyzed through qualitative-interpretive and quantitative-statistical procedures. The result of the study is not only interesting but also theoretically revealing. MABKBIA significantly outweighed MAKV (Conventional Model, i.e. the model employed by the experimental teacher in her teaching thus far) in all aspects of learning achievement. As for the mastery of language, students who were taught through MABKBIA generally scored significantly higher than those taught through MAKV. This is indicated by both quantitative and qualitative data showed that students taught through MABKBIA developed more supportive affective qualities than those taught through MAKV. Last, but not least, in terms of participation quality, those through MABKBIA participate in more engaged modes than those taught through MAKV. Those findings are theoretically predictable as far as MABKBIA is concerned. The superiority of MABKBIA in terms of language mastery may serve as empirical evidence of the superiority of modeling, scaffolding, and cooperative modes of learning on solitary and competitive models as well as experience in real-like communication events. In the meantime, more positive development of affective factors in MABKBIA lends a good support to the theory that comfortable situations are conducive for the development of affective factors supportive to the success of language learning. Finally, the more engaging modes of participation in MABKBIA support arguments that models of teaching are models of learning, and MABKBIA has succeeded in inviting students to participate more actively through its cooperative-yet-product-oriented approaches to language learning.